ANTIMICROBIAL RESISTANCE AND THE CHALLENGES OF MODERN THERAPY FOR THE CONTROL OF INFECTIONS CAUSED BY CORYNEBACTERIUM SP (Editora Impacto Científico, 2025)
Species of the genus Corynebacterium are Gram-positive, pleomorphic bacteria widely distributed in the environment and in the human microbiota, commonly described as "diphtheroids" when isolated from clinical samples. Although the iconic species is Corynebacterium diphtheriae, the agent of classic diphtheria, in recent years there has been a notable increase in the involvement of other Corynebacterium species (especially non-diphtheroids such as Corynebacterium striatum) as opportunistic or emerging pathogens in the hospital setting, associated with skin/soft tissue infections, implanted devices, joints, among others. For this reason, their antibiotic resistance has become a concern. Recent studies point to multiple resistance mechanisms, including genetic acquisition, chromosomal mutations, mobile elements, target alterations, and biofilm formation. This scenario has generated significant clinical and epidemiological challenges, requiring new therapeutic approaches. As promising alternatives, the use of natural compounds, such as essential oils and plant extracts, stands out, acting in a multifactorial way on the cellular structure and bacterial metabolism, reducing virulence and biofilm formation. In addition, secondary metabolites produced by Streptomyces and other actinobacteria have shown antimicrobial potential against Corynebacterium sp., interfering with cell wall synthesis and membrane integrity. Therefore, understanding the mechanisms of resistance and exploring alternative therapies are fundamental for the development of innovative and sustainable strategies to combat infections caused by Corynebacterium sp., contributing to the global fight against antimicrobial resistance.DOI: https://doi.org/10.56238/edimpacto2025.090-050